Coordinated expansion of memory T follicular helper and B cells mediates spontaneous clearance of HCV reinfection - Eisa, Mohamed; Gomez-Escobar, Elsa; Bédard, Nathalie; Abdeltawab, Nourtan F.; Flores, Nicol; Mazouz, Sabrina; Fieffé-Bédard, Alizée; Sakayan, Patrick; Gridley, John; Abdel-Hakeem, Mohamed S.; Bruneau, Julie; Grakoui, Arash; et al. (Frontiers in Immunology, 2024)
Follicular helper T cells are essential for helping maturation of B cells and production of neutralizing antibodies (NAbs) during primary viral infections. However, their role during recall responses is unclear. Here, we used hepatitis C virus (HCV) reinfection in humans as a model to study the recall collaborative interaction between circulating CD4 T follicular helper cells (cTfh) and memory B cells (MBCs) leading to generation of NAbs. We evaluated this interaction longitudinally in subjects who have spontaneously resolved primary HCV infection during a subsequent reinfection episode that resulted in either another spontaneous resolution (SR/SR, n=14) or chronic infection (SR/CI, n=8). Both groups exhibited virus-specific memory T cells that expanded upon reinfection. However, early expansion of activated cTfh (CD4+CXCR5+PD-1+ICOS+FoxP3-) occurred in SR/SR only. Frequency of activated cTfh negatively correlated with the time post infection. Concomitantly, NAbs and HCV-specific MBCs (CD19+CD27+IgM-E2-Tet+) peaked during the early acute phase in SR/SR, but not in SR/CI. Finally, the frequency of activated cTfh1 (CXCR3+CCR6-) subset correlated with neutralization breadth and potency of NAbs. These results underscore a key role for early activation of cTfh1 cells in helping antigen-specific B cells to produce NAbs that mediate clearance of HCV reinfection.